PROBLEMS OF IMPROVING PRODUCT COST CALCULATION METHODS (Marketing Journal, 2025)
This article analyzes the issues of improving product cost calculation methods based on national practices and international experience. The study scientifically evaluates the essence of full cost, direct costing, and ABC methods, their capabilities in cos t classification and allocation, and their impact on the financial stability of enterprises. Additionally, practical directions for modernizing cost accounting through the use of digital information systems, strengthening internal control, and refining accounting policies are substantiated.
Keywords: product cost; management accounting; full cost; marginal cost; direct costing; ABC method; cost classification; cost allocation; financial stability; economic efficiency. № 1 543